Pavement Design for Roads on Expansive Clay Subgrades (University of Khartoum Engineering Journal, 2022)
This paper aims to develop a design guide to help highway engineers in Sudan improve design and construction of pavement on expansive subgrades, thereby extending road life. Expansive soils as road subgrade in Sudan have been contributing to pavement failures and subsequently causing increased annual maintenance expenditure. The pavements design methods are found to be the primary cause of these failures. Thus, it is quite important to establish design criteria that can improve the road performance and durability. This design method was derived on basis of the technical design methods recommended by previous researchers and adopted by certain African countries as practical solutions of swelling problems of soil. To check the validity of the suggested design method, two cases of existingroads in Khartoum were studied. The results obtained clearly indicated that the suggested design method is effective and applicable in Sudan.